The novel bisphosphonate disodium dihydrogen-4-[(methylthio) phenylthio] methanebisphosphonate increases bone mass in post-ovariectomy rats - Aiko Takizawa; Mirei Chiba; Takeru Ota; Mayumi Yasuda; Keiko Suzuki; Takuya Kanemitsu; Takashi Itoh; Hisashi Shinoda; Kaoru Igarashi (Elsevier, 2016)
The novel bisphosphonate (BP) disodium dihydrogen-4-[(methylthio) phenylthio] methanebisphosphonate (MPMBP) is a non-nitrogen-containing BP with an antioxidant side chain that possesses anti-inflammatory properties. We investigated the systemic effects of this compound on bone loss induced by ovariectomy (OVX) in adult rats. Micro-computed tomography revealed that MPMBP increased bone mass and density in both the metaphysis and diaphysis, and improved the structural properties important for mechanical strength of osteoporotic bone. Sequential bone labeling with tetracycline and calcein indicated that MPMBP decreased longitudinal growth of the primary spongiosa (PS), but stimulated cortical bone formation in the diaphysis. MPMBP increased type I collagen accumulation in the PS, and decreased the number and size of adipocytes in the bone marrow, suggesting inhibition of increased bone marrow adipogenesis induced by OVX. Furthermore, MPMBP reduced the number of bone resorbing cathepsin K-positive osteoclasts induced by OVX. These results suggest that MPMBP could improve bone loss induced by estrogen deficiency. Both stimulation of bone formation and inhibition of bone resorption might play a role in the increase in bone mass and bone density after MPMBP treatment.